2022
DOI: 10.3390/su14020818
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sustainable Supply Chain Management on Company Performance Mediated by Competitive Advantage

Abstract: This study aims to examine the effect of sustainable supply chain management on company performance mediated by competitive advantage, the subjects of this study were the actors of the pottery Joint Business Group (JBG) in Banten Province, Indonesia. This type of research is quantitative research with descriptive research and causal research using questionnaires distributed directly to the JBG Pottery actors as many as 100 respondents. Moreover, Structural Equation Model (SEM) in the SmartPLS Software version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Sidek et al ( 2020 ) stated that the strategy of meeting customers’ needs helps halal SMEs to gain competitive advantage and subsequently, economic sustainability. This particular result was found similar with the result reported by Mukhsin and Suryanto ( 2022 ) on the positive influence of competitive advantage on sustainability. As such, the following hypothesis was proposed for testing:…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 92%
See 3 more Smart Citations
“…Sidek et al ( 2020 ) stated that the strategy of meeting customers’ needs helps halal SMEs to gain competitive advantage and subsequently, economic sustainability. This particular result was found similar with the result reported by Mukhsin and Suryanto ( 2022 ) on the positive influence of competitive advantage on sustainability. As such, the following hypothesis was proposed for testing:…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 92%
“…Table 5 presents the results on mediation effects, which supported H7a, H7b, H7c, H7d, and H7e. Mukhsin and Suryanto ( 2022 ) stated the crucial roles of technology, innovation, and network (internal resources) as well as customer orientation and competitor orientation (external resources) for SMEs to achieve competitive advantage by stimulating creative and innovative thoughts of achieving economic sustainability among entrepreneurs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sustainability practices enable the organizations to outperform their competitors by focusing on long-term stability. Given the illustration, the study found that sustainable supply chain practices provide the company with a sustainable competitive advantage with improved organizational performance ( 28 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%